The Effects of Occupational Violence on the Well-being and Resilience of Nurses - Rees, Clare; Wirihana, L.; Eley, R.; Ossieran-Moisson, R.; Hegney, D. (2018)
© 2018 Wolters Kluwer Health, Inc. All rights reserved. OBJECTIVE This article reports findings from a 2016 survey exploring the working life of nurses/midwives in Queensland, Australia. Responses related to occupational violence (OV) are reported. BACKGROUND OV is linked to high rates of burnout. It is imperative to continue efforts to understand how to avoid burnout and build nurse/midwives' resilience. METHODS A total of 2397 nurse/midwives working in Queensland responded to the survey and were asked to answer 8 questions related to OV. RESULTS In the last 3 months, 53% of nurses/midwives had experienced OV. Those respondents had significantly higher rates of burnout and lower resilience and rated the practice environment lower than their counterparts who had not experienced violence. CONCLUSIONS The experience of OV significantly impacts nurse resilience and levels of burnout. To retain nurses, attention must be given to reduce OV and support nurses who have experienced it.